The atlas of emergency radiology - Block, Jake; Jordanov, Martin I.; Stack, Lawrence B.; Thurman, R. Jason (McGraw-Hill Education/Medical, 2013)
This book features 1,500 outstanding radiologic images that depict virtually any condition encountered in an emergency department. Concise text side-by-side with the images details indications, key radiographic findings, and radiographic pearls. Allows readers to see what emergency conditions look like on CT, MRI, ultrasound, and x-ray. Ensures that radiographic signs won't be missed when radiology studies are reviewed in the emergency department